Implementasi Manajemen Bisnis dalam Novel Kedai Bunga Kopi Karya Rere - Apriliani Nurul Afifah; Ardelia Normalita; Eva Dwi Kurniawan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research will reveal the implementation of business management using the media of literary works carried out with the aim of knowing what management functions are carried out on the business. The literary work that will be used as a source of research data is a novel entitled Kedai Bunga Kopi Karya Rere. The problem presented is about how to apply management functions to business in the novel Kedai Bunga Kopi. This research is a type of qualitative research using hermeneutic methods or interpreting texts. Researchers can check their findings by utilizing the use of existing sources, methods, and theories. The conclusions obtained show that in this study there are four management functions applied in running a business, namely planning, organizing, directing, and controlling.